Hubungan Tingkat Pengetahuan Remaja Putri Tentang Kesehatan Reproduksi Dengan Perilaku Menstrual Hygiene - Florica Amanda (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
Menstrual hygiene is a component of individual hygiene in the form of measures to maintain the health and hygiene of the reproductive organs at the time of menstruation. Adolescent knowledge about reproductive health is still lacking, because good knowledge is a determining factor in maintaining reproductive health. This study aimed to know the relationship between learning and menstrual hygiene behaviour in adolescents in the class X senior high school no. 1 Kelapa in West Bangka province Bangka Belitung in 2017. The research design was an analytic survey using a cross-sectional method. The number of research samples was 80 people. The sampling technique used was total population. Data collection was conducted at Senior High School no. 1 of Kelapa, West Bangka, Bangka Belitung Province. The results showed that 54 respondents (66,2%) had negative menstrual hygiene behaviour, and 44 respondents (55,0%) had levels of insufficient knowledge, the results of statistical tests obtained p-value = 0.000 so that p < 0.05, then “Ho” is rejected which means there is a relationship between the level of knowledge of adolescent girls about reproductive health with menstrual hygiene behavior in adolescent girlswith the OR value between the level of lack of knowledge and the level of good knowledge OR = 12.667, meaning that respondents with a low level of knowledge have a tendency to behave negatively 12.6 times greater than respondents with a good level of knowledge.